IMPLEMENTATION OF STEM-BASED DIGITAL TRANSFORMATION TO IMPROVE SCIENCE LITERACY OF JUNIOR HIGH SCHOOL STUDENTS IN PADANGSIDIMPUAN CITY - Nasution, Nurhidaya Fithriyah; Nasution, Febriani Hastini; Harahap, Muhammad Syahril (Jurnal Pendidikan Matematika dan IPA, 2026)
The low level of science literacy among junior high school students, especially in regions such as Padangsidimpuan City, remains a major obstacle to delivering education that meets the demands of the 21st century. Digital transformation, combined with the STEM (Science, Technology, Engineering, and Mathematics) approach, is considered a promising solution by integrating technology into instruction and enhancing students"™ critical thinking abilities. This study aims to: (1) assess the science literacy levels of junior high school students in Padangsidimpuan City before and after the implementation of the instructional intervention; (2) describe the implementation of science learning designed around digital transformation and the STEM approach; and (3) evaluate its effectiveness in improving science literacy. A mixed-methods approach was adopted, utilizing a quasi-experimental design with a nonequivalent control group. Data were collected through science literacy assessments, classroom observations, student questionnaires, and interviews with both students and teachers. Quantitative data were analyzed using t-tests and normalized gain (N-Gain), while qualitative data were interpreted through thematic analysis. The findings demonstrate a significant increase in science literacy among students in the experimental group compared to those in the control group, with an average N-Gain of 0.62, categorized as moderate to high. The results suggest that science instruction incorporating digital transformation and the STEM approach is effective in improving students"™ science literacy and promoting active participation in the learning process. Moreover, this study produced a contextual digital learning module and offered policy recommendations to support science and technology-oriented education.